2011
DOI: 10.1017/s0033822200056599
|View full text |Cite
|
Sign up to set email alerts
|

Paired AMS 14C Dates on Planktic Foraminifera from a Gulf of Mexico Sediment Core: An Assessment of Stratigraphic Continuity

Abstract: ABSTRACT.A series of recent papers has called for multiple radiocarbon dates on planktic foraminifera to assess stratigraphic continuity in deep-sea sediment cores. This recommendation comes from observations of anomalous 14 C dates in planktic foraminifera from the same stratigraphic level. Potential reasons include bioturbation, downslope transport, secondary calcification, carbonate dissolution, and differential preservation. In this study, paired 14 C dates on dissolution-susceptible Globigerinoides ruber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Multiple studies of the sediments underlying Orca Basin have converged on a 7900 to 8500 yr timescale for the establishment of anoxic, hypersaline conditions in the basin (Addy and Behrens, 1980;Leventer et al, 1983;Meckler et al, 2008). For this study, we compared our radiocarbon values with the most recent foram record reported by Meckler et al (2008) because it includes a foraminiferal radiocarbon date in close proximity to the black-gray sediment transition depth and because radiocarbon analysis of individual foraminiferal species has confirmed stratigraphic continuity in this location (Flower et al, 2011). Adjusting these reported radiocarbon ages by the more recent, smaller reservoir age from the nearby Flower Garden Banks (Wagner et al, 2009) results in an 8700 ± 100 yr calendar age for Orca Basin brine.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies of the sediments underlying Orca Basin have converged on a 7900 to 8500 yr timescale for the establishment of anoxic, hypersaline conditions in the basin (Addy and Behrens, 1980;Leventer et al, 1983;Meckler et al, 2008). For this study, we compared our radiocarbon values with the most recent foram record reported by Meckler et al (2008) because it includes a foraminiferal radiocarbon date in close proximity to the black-gray sediment transition depth and because radiocarbon analysis of individual foraminiferal species has confirmed stratigraphic continuity in this location (Flower et al, 2011). Adjusting these reported radiocarbon ages by the more recent, smaller reservoir age from the nearby Flower Garden Banks (Wagner et al, 2009) results in an 8700 ± 100 yr calendar age for Orca Basin brine.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter, the mixing of sediments across a gradient of increasing abundance of a given foraminiferal species will introduce relatively abundant, younger foraminifera to older levels depleted in foraminifera down core (see example in Broecker et al, 1984 or Manighetti et al, 1995), contributing to bias the age of lower level to younger values. Conversely, dissolution or secondary calcification processes on fossilized shells, which furthermore do not occur equitably on all species (see Flower et al, 2011), could potentially deviate ages towards older values (Heier-Nielsen et al, 1995). These phenomena act on limited time scales, that is, few hundred years considering well-preserved faunas not affected by preferential dissolution (Broecker and Clark, 2011).…”
Section: Significance Of the Pelagic Fraction Within Core Md03-2693mentioning
confidence: 99%
“…After carefully considering the potential biases, we thus decided to construct an age model based on the radionuclide results and the AMS 14 C dates of mollusc shells only (Figure 3C, Table 1), these latter being considered in the literature to be most reliable even if the question is highly complex (e.g. Flower et al, 2011; Heier-Nielsen et al, 1995).…”
Section: Significance Of the Pelagic Fraction Within Core Md03-2693mentioning
confidence: 99%